Cosmopolitan Nationalism (A Theoretical Review) - Dwi Wandari Purwa Nugraha; Azmi Fitrisia (Pascasarjana, Universitas Negeri Padang, 2022)
especially Indonesia, because nationalism is a form of love and respect for the nation itself. However, the concept of nationalism has shifted due to the current of globalization which brings various understandings. One of them is cosmopolitanism which forces individuals to interact with ideas and symbols that come from outside their nation state. Then the concept of cosmopolitan nationalism emerged as nationalism that is relevant to be applied in the era of globalization which consists of the following aspects: nationality with the indicators being: achieving the ideals of a nation that is dynamic, not narrow-minded, maintaining national identity and loyalty to the state. Morals include: humanity, nationality, kinship and religion. Politics includes: tolerance, justice and responsibility. The Cultural Dimension includes: lifestyle, diversity, individual behavior, and global similarity.